MHD Mixed Convection Flow of Casson Fluid over a Moving Wedge Saturated in a Porous Medium in the presence of Chemical Reaction and Convective Boundary Conditions - Ullah, Imran; Shafie, Sharidan; Khan, Ilyas (Journal of Science and Technology, 2017)
This work concerned to hydromagnetic mixed convection flow of Casson fluid over a wedge. It is assumed that the wedge is moving inside a porous medium. The effects of chemical reaction, slip and convective boundary conditions at velocity, temperature and concentration walls are also considered. The governing partial differential equations are converted into ordinary differential equations using similarity transformations, and then solved by implicit finite difference scheme. Comparisons with the existing literature are performed and good agreement is achieved. The influence of physical parameters on flow fields are illustrated graphically. It is observed that the velocity rises with the increment in Casson fluid parameter and magnetic parameter. It is also noticed that thickness of thermal boundary layer grows with the increase of radiation. The skin friction coefficient enhances with the increase of porosity parameter while reduces as Casson fluid and moving wedge parameters increase. Increase in heat and mass transfer rate is noticed to be enhanced with the increase in radiation and chemical reaction parameters, respectively.